Penyusunan Album Keterampilan Hidup Sehari-Hari Untuk Anak Usia 2 - 6 Tahun Berdasar Pada Metode Montessori - Andri Anugrahana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
This study aims to describe the process of developing a teaching book for daily life skills for children ages 2 - 6 years based on Montessori method. This research uses research and development method, intending to (1) find out the procedure for developing daily life skill albums for children ages 2 - 6 years based on Montessori method and (2) describe the quality of the album. The research and development is modified from ten stages of Sugiyono and Borg and Gall, into five stages: 1) potential problems, 2) product design, 3) product validation by experts, 4) test instruments, and 5) limited trials. The result from expert validation for the purpose and method scored 3.75, considered in ‘good’ category. The content aspect scords 3, in ‘average’ category. The content aspect scored 3.5, in ‘good’ category. Overall, the result of expert validation showed the score of 3,4, and was considered as ‘good’.